Normalizacija baze podatkov s pomočjo teorije grafov - Nemec, Jože (Uporabna informatika (Ljubljana), 1994)
Determination of the higher order normal forms for database is frequently a time-consuming. We can make the work easy by applying graph theory. In the paper the necessary characteristics of database graphs and the corresponding matrics which describe the graphs are analyzed. The algorithm for designing database involving no redundancy, based on these characteristics is also presented.
Keywords: informatika; matematika; normalizacija; podatkovne baze; računalništvo; teorija grafov